Online journalism in 2015-2017. The media against technological platforms - Guallar, Javier (Anuario ThinkEPI, 2018)
A radiography of the state of digital media between 2015 to 2017 is presented. The main points discussed are: the media against technological platforms as Facebook and Google, the rise of the mobile reading of news and the problem of fake news.
Keywords: Journalism; Online journalism; Technological platforms; Infomediation; Facebook; Google; Mobile journalism; Mobile reading devices; Audience; Fake news.